Serum IgE Antibodies against Hazelnut in Hazelnut Processing Workers - Ege Gulec Balbay; Naciye Karatas; Peri Arbak; Songul Binay; Ozlem Yavuz; Ali Nihat Annakkaya; Oner Balbay; Umran Toru (The Scientific World Journal)
Aim. Previous studies have shown a higher sensitization rate to hazelnut in processing workers but no relation was found between the respiratory symptoms in workplace and hazelnut sensitization. Material and Method. To evaluate the association between the hazelnut sensitization and workplace-related respiratory complaints, hazelnut processing workers had undergone a questionnaire included work-related respiratory symptoms, smoking history, pulmonary function testing, and measurement of serum IgE antibodies against hazelnut. Results. This study consisted of 88 hazelnut processing workers (79 females and 9 males), aged 14–59 years (Mean ± SD: years). The mean working duration was months (min: 1–max: 180). Specific IgE against hazelnut allergens was positive in 14 of cases (17.1%). There was no significant difference between the cases with and without specific IgE against hazelnut allergens regarding respiratory symptoms, history of allergy, smoking status and spirometric values. Conclusion. 17.1% of the hazelnut processing workers were seropositive against hazelnut. Being sensitized to hazelnut was not found to be associated with work-related respiratory symptoms in this study. Further studies are needed in hazelnut workers respiratory health to search topics other than asthma.